Conflict in the shared household : domestic violence and the law in India - Jaising, Indira; Anurag, Pinki Mathur (New Delhi : Oxford University Press, 2019)
The objective of this publication is to take stock of the progress made towards achieving the statutory objectives ot the Protection of Women from Domestic Violence Act, 2005, in the first decade of its implementation. In this regard, the work attempts to cover themes relating to state accountability in terms of providing a supportive framework to facilitate women's access to justice, experiences in court, and jurisprudence evolved by appellate courts. It also seeks to trace and document the history behind the enactment of the PWDVA 2005.
This edition also issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on July 10, 2019).
Keywords: Family violence -- Law and legislation -- India; Family violence -- Social aspects -- India